2016
DOI: 10.1186/s12894-016-0183-1
|View full text |Cite
|
Sign up to set email alerts
|

Circumcision-related tragedies seen in children at the Komfo Anokye Teaching Hospital, Kumasi, Ghana

Abstract: BackgroundCircumcision is a common minor surgical procedure and it is performed to a varying extent across countries and religions. Despite being a minor surgical procedure, major complications may result from it. In Ghana, although commonly practiced, circumcision-related injuries have not been well documented. This study is to describe the scope of circumcision-related injuries seen at the Komfo Anokye Teaching Hospital in Kumasi, Ghana.MethodsThe study was conducted at the Urology Unit of the Komfo Anokye T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…It is possible that there are other late complications including urethrocutaneous fistulae, penile skin bridges, epidermal inclusion cysts and even glans or penile amputations that may not have reported to them. This is because most parents report late complications of circumcision to urologists and not to the circumciser as they do not attribute the complication to the circumcision procedure due to the long period it takes for the complications to manifest [3,7]. In Uganda, it was shown that even trained doctors needed to complete 100 circumcisions to significantly reduce the incidence of adverse events of circumcision [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that there are other late complications including urethrocutaneous fistulae, penile skin bridges, epidermal inclusion cysts and even glans or penile amputations that may not have reported to them. This is because most parents report late complications of circumcision to urologists and not to the circumciser as they do not attribute the complication to the circumcision procedure due to the long period it takes for the complications to manifest [3,7]. In Uganda, it was shown that even trained doctors needed to complete 100 circumcisions to significantly reduce the incidence of adverse events of circumcision [8].…”
Section: Discussionmentioning
confidence: 99%
“…In infants and neonates, it is safest to use techniques such as the device methods with Plastibel or Gomco clamp which protect the glans penis or use surgical techniques like the dorsal slit or sleeve technique where excision of foreskin is done with the glans penis in view to reduce the risk of injury to it [11]. In the study by Appiah et al on circumcision related tragedies in Ghana, almost 7% (5 out of 72) of the complications were penile amputations, mostly due to forceps guided/amputation technique [3]. In this study, the forceps guided technique/ amputation technique was the most common technique used despite the fact that in neonates and infants, this technique risks injuring the glans or the phallus due to its relatively small size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are numerous reports of circumcision complications, the most frequently known and reported complication is hemorrhage and wound site infection [4,5]. Urethral fistula is not a very common complication [6,7]. In this paper, we present a two-year-old male patient with severe penile and urethral trauma with severe urethral fistula after circumcision.…”
Section: Introductionmentioning
confidence: 98%